Isolated Horizontal Gaze Palsy: Observations and Explanations - Ewe, Renee; White, Owen B.; Burke, Ailbhe (Frontiers in Neurology, 2017)
We present three cases that we suggest require a novel diagnosis and a reconsideration of current understandings of pontine anatomy. In this case series, we highlight a series of patients with monophasic, fully-recovering inflammatory lesions in the pontine tegmentum not due to any of the currently recognized causes of this syndrome. We highlight other similar cases in the literature, and suggest there may be a particular epitope for an as-yet-undiscovered antibody underlying the tropism for this area. We highlight the potential harms of misdiagnosis with relapsing inflammatory or other serious diagnoses with significant adverse impact on the patient. In addition, we propose that this would support a reinterpretation of the currently accepted anatomy of the pontine gaze inputs to the MLF and PPRF.